2014
DOI: 10.1007/s12134-014-0405-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Diversity in the Phenomenon of Immigrant Organizations: A Comprehensive Framework

Abstract: Voluntary immigrant organizations are a worldwide phenomenon. Yet, despite the fact that all of these organizations were founded as a consequence of immigration, their actual characteristics and activities are very diverse, and even in some cases, immigrants do not found organizations at all. Therefore, this paper deals with the question: under which conditions are different associations founded-and when are they not founded? Following a brief mapping of the wide category of immigrant organizations, the paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 46 publications
2
21
0
1
Order By: Relevance
“…Prior research has shown that IOs are embedded in multiple contexts that can foster new opportunities and resources for immigrant communities (Babis 2016;Vermeulen et al 2016). Findings revealed here, however, complement this narrative by demonstrating how the embeddedness of immigrant organizations in multilayered domestic, homeland, and geopolitical contexts, can also contribute to the stigmatization and constraining of immigrant organizational capacities.…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations
“…Prior research has shown that IOs are embedded in multiple contexts that can foster new opportunities and resources for immigrant communities (Babis 2016;Vermeulen et al 2016). Findings revealed here, however, complement this narrative by demonstrating how the embeddedness of immigrant organizations in multilayered domestic, homeland, and geopolitical contexts, can also contribute to the stigmatization and constraining of immigrant organizational capacities.…”
Section: Discussionsupporting
confidence: 42%
“…Immigrant organizations are meso-level conduits, which help facilitate immigrant integration, civic incorporation, mobilization, and transnational engagement (Babis 2016;Chaudhary and Guarnizo 2016). This article introduced the concept of ascriptive organizational stigma and used it to investigate how domestic and geopolitical contexts can lead to the stigmatization and constraining of Pakistani immigrant organizations in New York City and London.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, diaspora engagement in philanthropy has intersected with the building of diaspora communities and political mobilization. Indeed, diaspora mobilization and organizations of many kinds emerge and “shape collective identity” (Babis, 2016). For example, Liberatore’s (2017) research maps out the Somali diaspora in the United Kingdom, which mobilized and protested in 2013 due to Barclays Bank’s decision to shut down accounts which hosted money transfers (Liberatore, 2017).…”
Section: Diaspora Philanthropy To the Homelandmentioning
confidence: 99%